المشكلات السلوكية في الوسط المدرسي وآليات المواجهة المقررة في التشريع - حبوسة أبوبكر (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
The research aims to identify the various behavioral problems prevalent in the school environment, while clarifying the coping mechanisms that the school administration uses to reduce these problems. These mechanisms were represented in giving priority to the preventive educational measures represented by the listening and psychological and educational follow-up cell, over the purely administrative procedures represented by the disciplinary council.